A framework for effective construction workers safety training using flipped learning - Rehman, Abdul; Hassan, Muhammad Usman; Zubair, Muhammad Umer; Aziz, Taha; Ahmed, Khursheed (Journal of Civil Engineering and Management, 2025)
Effective safety training plays an important part in safety management on construction sites. Construction workers safety and safety training education remain to be the main issues in the construction industry, as current practices rely on traditional methods. These methods often lack classroom interaction, hindering active worker engagement and fail to accommodate diverse learning paces and styles. To enhance safety awareness among workers, there is a need for a more effective system for safety training programs within the construction industry. Therefore, this study aims to comprehensively analyse an experimental intervention using flipped learning to reduce costs and enhance learning outcomes in construction safety training. Flipped learning transforms traditional classroom learning by introducing students to web-based videos, presentations, and readings before class, freeing up in-class time for discussions and problem-solving. An intervention study was carried out to confirm the effectiveness of flipped learning approach within the construction industry. In this study, 40 personnel from a leading construction firm in Pakistan underwent safety training, with 20 following the traditional method and the remaining 20 following the proposed flipped model. The final quiz revealed a score increase from 27.9 to 31.5 in flipped learning, indicating a 12.90% increase. Based on these findings, it is suggested that adopting the flipped learning approach leads to better learning outcomes within the construction industry, as workers can pause, rewind, and replay the lectures at their leisure. This not only makes safety training more accessible but also enhances on-site safety in a cost-effective manner.